The protective role of the recombinant IL-2 in complex therapy of cystic ovarian endometriosis in patients of advanced reproductive age - E. I. Sokolova; I. I. Kutsenko; E. I. Kravtsova; S. K. Batmen (Медицинский вестник Юга России, 2019)
Objective: tto estimate the potential of the protective effect of recombinant IL-2 on the ovarian reserve of patients in advanced reproductive age after enucleation of a cystic ovarian endometriosis (COE).Materials and methods: Initially and over a year after laparoscopic ovarian cystectomy using hemostatic material based on oxidized cellulose, 63 patients with a single-sided COE (4-7 cm) were examined, age group: 36-45 years old. The levels of cytokines (IL-6, IL-2, IL-10, TNF), the content of diene conjugates of unsaturated fatty acids, malonic dialdehyde, superoxide dismutase and the level of molecules of average weight were determined in the peritoneal fluid and peripheral blood. The comparative analysis of the ovarian reserve (the antral follicle count (AFC) and the level of Anti-Mullerian hormone (AMH)) was conducted between 32 patients receiving adjuvant dienogest therapy (6 months) with additional administration of recombinant IL-2 and 31 patients receiving only dienogest.Results: When recombinant IL-2 is used in the early postoperative period, AFС (both, in the intact and operated ovary) and the AMH level (later restored to the results of the initial parameters) increase statistically significant.Conclusions: Recombinant IL-2 compensates the initial deficiency of the regulatory cytokine, reduces the proapoptotic effect on ovarian tissue, and activates antioxidant systems. When used in postoperative period of the complex therapy (IL-2 and dienogest), the ovarian reserve remains almost at the initial level, which favors the implementation of reproductive plans and reduces the likelihood of premature menopause.